Cambodia: The winner takes it all. 2018 elections set country firmly on path towards authoritarianism - Chandarin Chum; Felix Heiduk (Stiftung Wissenschaft und Politik (SWP), 2018)
There was never any doubt who would win Cambodia's 2018 elections, with electoral politics skewed to favour Hun Sen's ruling Cambodian People's Party (CPP). The CPP has already declared victory, claiming 76 per cent of votes and all of the 125 parliamentary seats. The elections were condemned as a 'sham' by the opposition after the dissolution of the Cambodia National Rescue Party (CNRP), the imprisonment of CNRP leader Kem Sokha, and a crackdown on civil society and the media. These events mark a watershed in Cambodian politics, indicating the establishment of a single-party autocracy backed by China.
Keywords: 320